Vestibular migraine: diagnosis challenges and need for targeted treatment - Felipe Barbosa; Thaís Rodrigues Villa (Arquivos de Neuro-Psiquiatria)
ABSTRACT Approximately 1% of the general population suffers from vestibular migraine. Despite the recently published diagnostic criteria, it is still underdiagnosed condition. The exact neural mechanisms of vestibular migraine are still unclear, but the variability of symptoms and clinical findings both during and between attacks suggests an important interaction between trigeminal and vestibular systems. Vestibular migraine often begins several years after typical migraine and has a variable clinical presentation. In vestibular migraine patients, the neurological and neurotological examination is mostly normal and the diagnosis will be based in the patient clinical history. Treatment trials that specialize on vestibular migraine are scarce and therapeutic recommendations are based on migraine guidelines. Controlled studies on the efficacy of pharmacologic interventions in the treatment of vestibular migraine should be performed.